Back Cover: Divalent Thulium Triflate: A Structural and Spectroscopic Study (Angew. Chem. Int. Ed. 15/2017). Issue 15 (8th March 2017) - Xémard, Mathieu; Jaoul, Arnaud; Cordier, Marie; Molton, Florian; Cador, Olivier; Le Guennic, Boris; Duboc, Carole; Maury, Olivier; Clavaguéra, Carine; Nocton, Grégory
Abstract : Divalent thulium complexes have great potential in reductive organic chemistry and for small‐molecule transformations. Nonetheless, they are rare and hard to synthesize, thus their electronic structure is almost unexplored. In their Communication onpage 4266 ff., G. Nocton et al. present a first step to the discovery of the submerged part of the iceberg, through unravelling the ground‐state nature of divalent thulium triflate by means of luminescence, magnetism, and EPR spectroscopy.